FAKTOR DETERMINAN KECURANGAN LAPORAN KEUANGAN DENGAN PENDEKATAN TEORI FRAUD HEXAGON - Ria Khafifa; Harti Budi Yanti (EBID: Ekonomi Bisnis Digital, 2025)
This research aims to determine the effect of each element of the Fraud Hexagon on financial statement fraud. The independent variables used in this research are financial stability, ineffective monitoring, change in Auditor, CEO’s education, CEO’s duality, and cooperation with the Government. While the dependent variable used in this research is financial statement fraud. The objects of this research are Industrial and Transportation & Logistics sector companies listed on the IDX in 2021 – 2023 with a total sample of 228. The analysis technique in this research is multiple linear regression analysis of panel data using EViews for the test. The results of this research indicate that ineffective monitoring and CEO’s education have a positive effect on financial statement fraud, while financial stability, change in Auditor, CEO’s duality, and cooperation with the Government have no effect on financial statement fraud.